Análisis jurídico y doctrinario de la sentencia sobre el acoso laboral No. 986-19-jp/21 y acumulados - Gualán Sánchez, Pamela Michelle (2023)
This thesis arises from the interest in investigating how harassment at work operates in public and private institutions, as well as how this problem is dealt with in complaints filed with the Ministry of Labour. Harassment at work is a latent and even silent reality that develops in all work environments, generating a psychological and physical affectation for those who are victims of this type of violence; this phenomenon not only has consequences for the worker, but also for his or her family and work environment. It was determined that, in order to be determined, harassment at work is essential to comply with certain characteristics. The study carried out in this judgment analysis seeks to demonstrate the violation of the constitutional and legal rights of workers when there are manifestations of harassment in the workplace and the lack of diligence on the part of the organism in charge of resolving these cases. In addition, the criteria issued by the Constitutional Court in the four review processes of the judgment under analysis No. 986-19-JP/ 21 were analyzed, paying special attention to the decision taken regarding the rights that were violated, as well as the judgment No. 1292-19-EP/21, which is related to the issue raised. In the present work, materials and methods were applied, which allowed the development of the field study of the research, applying surveys and interviews with legal professionals, which provided and extracted relevant information for the verification of the objectives set out in the degree project. The fundamental purpose of this research is to form a legal criteria regarding the resolutions of the Ministry of Labour, and the lack of a normative that regulates everything in terms of the problems raised. It is important to study the proposed topic as it is a type of violence that has always been exercised in the workplace; in our legislation it has only been in place for a few years in the 2017 reforms of the Labour Code and in the Organic Law of Public Service on workplace harassment, which has meant that workers are not properly informed, which means that the topic is not relevant in the workplace, allowing this phenomenon to spread and making more difficult to eradicate. Furthermore, due to lack of knowledge of the norms, attributions and power of the organism in charge of processing these cases, a series of transgressions of workers' rights have been witnessed, such as: right to effective judicial protection and effective administrative protection, the right to formal and material equality, the right to decent work, right to non-discrimination based on the basis of ethnicity, place of birth, age, sex, gender identity, disability or any other distinction.